Citizen-Based Arts Festivals in North Sumatra: Obstacles, Solutions, and Social Impacts - Togatorop, Merdy Roy Sunarya; Hakim, Ifwanul; Mulya, Aqsa; Erizon, Erizon (Universitas Negeri Medan, 2025)
This art study aims to reveal a new phenomenon of organizing art festivals based on community mutual cooperation or better known as citizen festivals. This study is based on the desire to produce a view and knowledge in seeing the challenges, solutions, and social impacts of citizen festivals. The study focuses on three citizen festivals representing three geocultural regions of North Sumatra, namely coastal, mountainous, and urban. The purpose of this study is to find the challenges faced by organizers in implementing Community-Based Art Festivals in North Sumatra and to reveal their solutions in facing these challenges, as well as to find the social impact of organizing Community-Based Art Festivals for the surrounding community. The method used in this study is a qualitative approach. The process of searching for data and information is carried out using interview, documentation, and literature study methods. The results of the study show that community-based festivals in coastal, mountainous, and urban areas have their own challenges. The Berhala Island marine culture festival on the Serdang Bedagai coast must deal with uncertain natural conditions. The Pancur Siwah Festival in the Karo mountains must grapple with religious ethics, the conservative attitude of the elders and the apathy of the younger generation. Meanwhile, the Jawa Deli Festival in Medan must be adaptive and collaborative with a multicultural social environment by facilitating various ethnicities. Some categories of impacts generated from these three types of festivals are cultural impacts, educational impacts, and economic impacts.